Investigating the mechanisms of secretion of the moonlighting proteins Enolase and Fructose-1, 6-Bisphosphate Aldolase in Neisseria meningitidis - Atwah, Banan (2019)
Neisseria meningitidis is an obligate commensal of humans that mainly colonises the nasopharynx. It is also an important cause of serious diseases, such as meningitis and sepsis. N. meningitidis uses several secretion systems (type I, type Va, type Vb, and type Vc) for secreting proteins, which enable the bacteria to modulate their cell surface and evade the human immune system.